2022
DOI: 10.1177/03635465221094816
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bilaterality in Patients With 1 Posterosuperior Rotator Cuff Tear

Abstract: Background: In patients with a known unilateral posterosuperior rotator cuff tear (PSRCT), the ability to predict a contralateral PSRCT may assist in earlier diagnosis and improved patient outcomes. Purpose: To determine factors associated with bilateral PSRCT and their most predictive combinations using a nonhospitalized general population. Study Design: Cross-sectional study; Level of evidence, 3. Methods: This study involved 736 individuals (n = 1472 shoulders) drawn from a rural cohort. PSRCT was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Of cases with RCTs on one side, contralateral RCTs have been reported to occur in 25.1%–38.6% of cases in the general population. 11 , 28 However, there are a few reports on the contralateral shoulder of patients undergoing ARCR with or without a RCT. In this study, RCTs in the contralateral shoulder of the ARCR were evaluated by US, and their prognosis was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of cases with RCTs on one side, contralateral RCTs have been reported to occur in 25.1%–38.6% of cases in the general population. 11 , 28 However, there are a few reports on the contralateral shoulder of patients undergoing ARCR with or without a RCT. In this study, RCTs in the contralateral shoulder of the ARCR were evaluated by US, and their prognosis was investigated.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Gwark et al reported that age ≥61 years, manual labor, critical shoulder angle ≥35, retraction degree of Patte ≥ grade 2, biceps tendon injury, and metabolic syndrome were significantly associated with bilateral posterosuperior RCTs. 11 Yamaguchi et al reported that the presence of rotator cuff disease was highly correlated with age; the average age was 48.7 years for patients with no RCT, 58.7 years for those with a unilateral tear, and 67.8 years for those with a bilateral tear. 33 In this study, the mean age of the patients was 64.7 years, and with respect to shoulder activity in jobs and sports, 65 (62.5%) patients were active, suggesting a relatively high incidence of bilateral RCTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation